Nitrogen Fixation And Vegetative Growth Of Immature Oil Palm Inoculated With Bacillus Sphaericus (Strain Upmb-10) - Ab. Aziz, Zakry Fitri (2008)

(untitled)
Inorganic-N fertilizer is the most widely used input in agriculture and it is a major factor that limits crop growth and yield. However, excessive use of inorganic nitrogenous fertilizer could lead to hazardous effect to the agro-environment. Besides that, it would also increase total production cost of the agricultural sector especially in the oil palm industry, the largest income generator to Malaysian agricultural economy. Rapid losses of fertilizer-N through leaching would further increase the cost on oil palm production and make the sector less profitable. In recent times, there is an increased attention to biological nitrogen fixation (BNF) as an alternative or supplement to nitrogenous fertilizers through application of associative N2-fixing rhizobacteria which could be applied to oil palm. These beneficial plant growth promoting rhizobacteria (PGPR) have been reported to be efficient in fixing atmospheric nitrogen and stimulating growth of leguminous and non- leguminous crops. Thus, it could be used as a biofertilizer and bioenhancer for most crops. However, there has been no report on the beneficial effect of PGPR on early growth of young oil palms under field conditions. A field trial using 15N isotope was conducted to estimate the N2 fixing capacity of a single strain N2-fixing rhizobacterium, Bacillus sphaericus UPMB-10, and assess its effects on early growth of young oil palms. Results from a 240-day (D240) field experiment indicated that the Bacillus sphaericus rhizobacterial strain UPMB-10 is a potential biofertilizer for oil palm seedlings with a N2 fixing capacity of 63% Ndfa (N derived from atmosphere) (78 g N2 fixed palm-1) of the total N requirement of young oil palms (equivalent to 12 kg N ha-1 at 148 palms ha-1) over 8 months. B. sphaericus UPMB-10 inoculation stimulated higher N content (125 g palm-1) as compared to the uninoculated control (90 g palm-1) and also promoted a total dry matter accumulation of 11 kg palm-1 in comparison to the control, 8 kg palm-1. Present study also showed significant differences in two of the four physical parameters (leaflet numbers, rachis lengths, cross-sections of petioles and leaf area) of vegetative growth of young oil palm inoculated with strain UPMB-10 at D120. B. sphaericus UPMB-10 inoculation stimulated leaflet numbers and leaf area at 123.4 ± 2.5 and 1.57 ± 0.05 m2, respectively, as compared to Uninoculated + 2/3Ni palms at 115.6 ± 2.2 and 1.43 ± 0.05 m2, respectively, at D120. However, no significant response was observed at D240. Thus, the study showed that the significant total N2 fixed does not correlate significantly with physical parameters at the later stage (D240) of vegetative growth. This phenomenon is caused by unstable development of immature oil palm under field planting. This was also true for dry matter and Total-N yield analyses at D240 which were not statistically significant although they showed incremental trends. The frond (leaflets plus rachis) of the young oil palm is the most likely vegetative component to be adopted as representative of the whole palm for future N2 fixation studies based on the % Ndfa values of the frond (70%) and whole palm (63%) which did not deviate significantly. This new approach will make such field studies more cost effective and time saving. B. sphaericus UPMB-10 inoculation is more effective in delivering N to the immature palms than nitrogenous fertilizer. The reduction (63%) in inorganic-N fertilizer rates due to the incorporation of the inoculum and the resultant N2 fixation could subsequently reduce the cost of nitrogenous fertilizer. The above findings provided evidence that locally isolated B. sphaericus UPMB-10 has the potential to effectively supplement inorganic-N fertilizer for sustainable cultivation of young oil palm.